ChemBrain como recurso didáctico para el aprendizaje de Química Orgánica con los estudiantes de Sexto semestre de la Carrera de Pedagogía de la Ciencias Experimentales Química y Biología - Colcha Pala, Dayana Carolina (2025)
The current study, titled "ChemBrain as a Teaching Resource for Learning Organic Chemistry with Sixth-Semester Students attending the Pedagogy of Experimental Sciences in Chemistry and Biology academic program at Chimborazo National University," aimed to design and implement a digital teaching tool grounded in the 5E instructional model. The integration of digital resources like ChemBrain is essential for enhancing learning experiences and adapting to evolving educational demands. A non-experimental, quantitative research design was employed, involving 27 students as participants. Data were collected through surveys and supported by descriptive, bibliographic, and field-based analysis. The findings indicate a high level of student acceptance of ChemBrain, particularly valuing its user-friendly interface and the interactive educational activities it facilitated. The results underscore the importance of incorporating diverse, technology-enhanced teaching tools to improve comprehension and engagement in complex subjects like Organic Chemistry